Environmental Education for Healthy Childhoods: Exploring Sanitation Awareness and Nutritional Behavior among School-Age Children - Yuliyanti Setiawati; A. Bida Purnamasari; Erma Suryani Sahabuddin; Eka Apriyanti (Al-Musannif, 2026)
This phenomenological study explored school-age children’s lived experiences of environmental sanitation awareness and nutritious dietary behavior within environmental education in South Sulawesi, Indonesia. Using a qualitative design, data were collected through in-depth interviews, participant observation, and documentation involving school-age children, parents, and teachers selected purposively from elementary and junior secondary schools. Thematic phenomenological analysis revealed five interrelated themes: developing sanitation awareness through daily practices, family and school as nutritional learning spaces, environmental education as behavioral transformation, social and cultural influences on healthy living, and healthy living as a shared responsibility. The findings indicate that children’s understandings of hygiene and healthy eating are shaped less by formal instruction than by repeated interactions, role modeling, and experiential learning in home, school, and community settings. Environmental education emerged as a meaningful framework for connecting sanitation, nutrition, and child well-being by fostering responsibility, comfort, and environmental care. The study implies that schools and families should collaborate to embed sanitation literacy and nutritional awareness into everyday routines and child-centered environmental programs.